C++ core guidelines explained : best practices for modern C++ - Grimm, Rainer (Addison-Wesley, 2022)
Write More Elegant C++ Programs "We are very pleased to see Rainer Grimm applying his teaching skills and industrial background to tackling the hard and necessary task of making the C++ Core Guidelines accessible to more people." --Bjarne Stroustrup and Herb Sutter, co-editors, C++ Core Guidelines The official C++ Core Guidelines provide consistent best practices for writing outstanding modern C++ code and improving legacy code, but they're organized as a reference for looking up one specific point at a time, not as a tutorial for working developers. In C++ Core Guidelines Explained, expert C++ instructor Rainer Grimm has distilled them to their essence, removing esoterica, sharing new insights and context, and presenting well-tested examples from his own training courses. Grimm helps experienced C++ programmers use the Core Guidelines with any recent version of the language, from C++11 onward. Most of his code examples are written for C++17, with added coverage of newer versions and C++20 wherever appropriate, and references to the official C++ Core Guidelines online. Whether you're creating new software or improving legacy code, Grimm will help you get more value from the Core Guidelines' most useful rules, as you write code that's safer, clearer, more efficient, and easier to maintain. Apply the guidelines and underlying programming philosophy Correctly use interfaces, functions, classes, enum, resources, expressions, and statements Optimize performance, implement concurrency and parallelism, and handle errors Work effectively with constants, immutability, templates, generics, and metaprogramming Improve your C++ style, manage source files, and use the Standard Library Register your book for convenient access to downloads, updates, and/or corrections as they become available. See inside book for details.